(untitled) (Global Journal of Science Frontier Research, 2016)
This research focuses on the synthesis of metal-containin gmesoporous silica for catalytic esterification of benzyl alcohol with acetic acid. In this study Zr-containing MCM-41 with different molar ratios of Si/Zr were synthesized successfully. It is observed that the structural ordering of Zr-MCM-41varies with the Si/Zr ratio, and highly ordered mesoporous molecular sieves could be obtained for a Si/Zr molar ratio larger than 5. Calcination may significantly improve the structural regularity. In esterification reaction of benzyl alcohol with acetic acid, the benzyl alcohol conversion over all the Zr-MCM-41catalysts linearly increases with increasing the reaction temperature and selectivity to benzyl acetate was 100 %. The molar ratios of reactants also were investigated for final product yield; the molar ratio of acetic acid to benzyl alcohol can be 2:1 for high yield.